Drop Interface Coalescence in Liquid-Liquid System - K . Harweel, Cecelia; M. Rasheed, Asseel (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
This investigation is a study of the length of time where drops can exist at an oil-water interface before coalescence take place with a bulk of the same phase as the drops. Many factors affecting the time of coalescence were studied in is investigation which included: dispersed phase flow rate, continuous phase height, hole size in distributor, density difference between phases, and viscosity ratio of oil/water systems, employing three liquid/liquid systems; kerosene/water, gasoil/water, and hexane/water. Higher value of coalescence time was 8.26 s at 0.7ml/ s flow rate, 30cm height and 7mm diameter of hole for gas oil/water system, and lower value was 0.5s at 0.3ml/s flow rate, 10 cm height and 3mm diameter of hole for hexane/water system. It is observed that time of coalescence increased with increase in the dispersed phase flow rate, continuous phase height, hole size in distributor, and viscosity ratio of oil/water system. The results have been analyzed by dimensional and statistical analysis, and a correlation was developed relating coalescence time with the operating/actors and the physical properties of the three oil/water systems.